If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying X + -6 + -20 = 142 Reorder the terms: -6 + -20 + X = 142 Combine like terms: -6 + -20 = -26 -26 + X = 142 Solving -26 + X = 142 Solving for variable 'X'. Move all terms containing X to the left, all other terms to the right. Add '26' to each side of the equation. -26 + 26 + X = 142 + 26 Combine like terms: -26 + 26 = 0 0 + X = 142 + 26 X = 142 + 26 Combine like terms: 142 + 26 = 168 X = 168 Simplifying X = 168
| 6b+16=4 | | 25*w*1=0 | | 6[3a+1]-30=3[2a-4] | | 15+2x=2x | | 5x+2(5x-15)=-60 | | I2/3z=9 | | 11-(9x)+2x-(-9)= | | r=d/1-t | | (-t/2)=12 | | 7*z*0=0 | | -11=4a-3 | | -8(1-7n)+7(n+3)= | | 5n-3n+7+2n= | | 24a+72b-40c= | | 13*0*p=0 | | 6j-4j+12=6j-3j+30 | | 42-48v=-54 | | 9=8-x/4 | | 4(2a)-a= | | 4w-5=12w-4 | | (4x^2-1)(6x^2-9)= | | 5(d+5)+2d=-13-8d | | 1/3x-8=4/9x | | 20=a/9 | | 26=13/v | | -7(3a-2)+4(5a+5)= | | 10=6+(1+3m)-2(2+10m) | | X-y=110 | | 7x-3x(x+1)= | | 6+2[3j-2]=4[1+j] | | 1/y-1/2=4 | | 6(z/2-5)=36 |